Five Children And IT - Nesbit, E. (Lahore Readings, 2017)
"It" is a Psammead, a sand fairy which gives the children a wish a day; their wishes bring much excitement but often a lot of trouble too.
Include Illustrations
Keywords: Fairies -- Wishes -- Brothers and sisters